1993
DOI: 10.1099/0022-1317-74-4-785
|View full text |Cite
|
Sign up to set email alerts
|

Replication and encapsidation of the viroid-like satellite RNA of lucerne transient streak virus are supported in divergent hosts by cocksfoot mottle virus and turnip rosette virus

Abstract: Cocksfoot mottle sobemovirus supports replication and encapsidation of the viroid-like satellite RNA (sat-RNA) of lucerne transient streak virus (LTSV) in two monocotyledonous species, Triticum aestivum and Dactylis glomerata. Additionally, LTSV sat-RNA replicates effectively in the presence of turnip rosette sobemovirus in Brassica rapa, Raphanus raphanistrum and Sinapsis arvensis, but not in Thlaspi arvense or Nicotiana bigelovii, indicating that host species markedly influence this interaction. Previous rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
2

Year Published

1997
1997
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 23 publications
0
15
0
2
Order By: Relevance
“…For example, Sehgal et al (1993) found that replication and encapsidation of the viroidlike satellite RNA of lucerne transient streak virus (LTSV) were supported in the presence of turnip rosette sobemovirus (TROV) in crucifer species S. arvensis, B. rapa, and R. raphanistrum, but not in T. arvense, indicating that host species markedly influenced this interaction.…”
Section: Response To Other Human Manipulationsmentioning
confidence: 99%
“…For example, Sehgal et al (1993) found that replication and encapsidation of the viroidlike satellite RNA of lucerne transient streak virus (LTSV) were supported in the presence of turnip rosette sobemovirus (TROV) in crucifer species S. arvensis, B. rapa, and R. raphanistrum, but not in T. arvense, indicating that host species markedly influenced this interaction.…”
Section: Response To Other Human Manipulationsmentioning
confidence: 99%
“…Viral host ranges can be extended by the presence of other viral systems. For example, Sehgal et al (1993) found that replication and encapsidation of the viroid-like satellite RNA of lucerne transient streak virus (LTSV) were supported in the presence of turnip rosette sobemovirus (TROV) in crucifer species S. arvensis, Brassica rapa, and Raphanus raphanistrum, but not in Thlaspi arvense, indicating that host species markedly influenced this interaction. Mamula et al (1997) indicated that S. arvensis could serve as a potential host plant to belladonna mottle (BeMV, isolate from Croatia) and turnip yellow mosaic tymoviruses (TYMV, isolate from Slovenia) in greenhouse studies.…”
Section: Response To Parasitesmentioning
confidence: 99%
“…For example, Sehgal et al (1993) found that replication and encapsidation of the viroid-like satellite RNA of lucerne transient streak virus (LTSV) were supported in the presence of turnip rosette sobemovirus (TROV) in R. raphanistrum.…”
Section: Response To Parasitesmentioning
confidence: 99%